Navigating Great Lakes Hydroclimate Data - Fry, Lauren M.; Gronewold, Andrew D.; Seglenieks, Frank; Minallah, Samar; Apps, Deanna; Ferguson, Jamie (Frontiers in Water, 2022)
Despite the fact that the Great Lakes contain roughly 20% of the world’s surface freshwater, there is a relatively limited body of recent work in peer reviewed literature that addresses recent trends in lake levels. This work is largely coming from a handful of authors who are most well versed in the complexities of monitoring and modeling in a basin that spans an international border and contains vast areas of surface water connected by both natural and managed connecting channel flows. At the same time, the recent dramatic changes from record low water levels in the early 2010s to record high water levels across the Great Lakes in 2019 and 2020 have brought significant attention to the hydroclimatic conditions in the basin, underscoring the need to bring new approaches and diverse perspectives (including from outside the basin) to address hydroclimate research challenges in the Great Lakes. Significant effort has led to advancements in data and model coordination among U.S. and Canadian federal agencies throughout the decades, and at the same time research from the broader community has led to higher resolution gridded data products. In this paper, we aim to present the current state of data and models for use in hydrological simulation with the objective of providing a guide to navigating the waters of Great Lakes hydroclimate data. We focus on data for use in modeling water levels, but we expect the information to be more broadly applicable to other hydroclimate research. We aim to include diverse perspectives by including not only authors from federal agencies providing data on both sides of the border, but also authors who came from outside the basin to conduct research within the Great Lakes.